PENGATURAN ZONASI DI DAERAH SEMPADAN SUNGAI MANDAR, KECAMATAN TINAMBUNG KABUPATEN POLEWALI MANDAR - Ali Akbar Tasrif; Rita Tahir Lopa; Farouk Maricar (LPPM Universitas Abdurrab, 2022)
Mandar River is one of the rivers in West Sulawesi Province which is located in Polewali Mandar Regency and comes from one of the foot of the mountain with a length of about 150 km. The use of Mandar River water, apart from being a source of air for the surrounding community, is also used as a power plant, so that the Mandar River cannot be separated from the lives of some people who live in the border areas of the Mandar River. Over time, activities in the Mandar River border area have increased, especially in the construction of residences and other buildings such as residential buildings. This study aims to identify the use of space in the Mandar River border area and provide recommendations for spatial planning by zoning the use of space in the area and reducing the impact of flooding. The method used in this research is descriptive qualitative with spatial analysis. The results of this study are the zoning arrangements for regional activities in the form of conservation areas and border areas, while the zoning of cultivation areas are river conservation areas and agricultural and plantation areas. The border area of ​​the Mandar River for structuring more arrangements is right on the edge, where the area is a flood-prone area with relocation development or river normalization.